2018
DOI: 10.2147/dmso.s178674
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sleep quality and its predictors among patients with diabetes in Jazan, Saudi Arabia

Abstract: BackgroundPoor sleep quality is common among patients with diabetes. It is associated with negative physical, psychological, and functional consequences. However, the implicated risk factors of poor sleep quality remain uncertain.ObjectivesThis study aimed to determine the prevalence of poor sleep quality among patients with diabetes and to investigate the factors associated with the poor sleep quality.Patients and methodsAn analytical cross-sectional study of 307 diabetic patients in Jazan, Saudi Arabia was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 35 publications
5
18
1
Order By: Relevance
“…In this study, age, sex and BMI were not significantly associated with sleep quality. This is in contrast to the findings of a study conducted by Darraj et al [22] that showed that being elderly, female and having an abnormal BMI were significantly associated with poor sleep quality. A possible reason why this current study did not find these factors to be significant is that the majority of the participants were elderly women with abnormal BMI, meaning age, sex and BMI differences could not be fully assessed.…”
Section: Factors Associated With Sleep Qualitycontrasting
confidence: 99%
See 3 more Smart Citations
“…In this study, age, sex and BMI were not significantly associated with sleep quality. This is in contrast to the findings of a study conducted by Darraj et al [22] that showed that being elderly, female and having an abnormal BMI were significantly associated with poor sleep quality. A possible reason why this current study did not find these factors to be significant is that the majority of the participants were elderly women with abnormal BMI, meaning age, sex and BMI differences could not be fully assessed.…”
Section: Factors Associated With Sleep Qualitycontrasting
confidence: 99%
“…In this study, the presence of complications was a significant predictor of sleep quality. This finding is congruent with previous studies [22,47,48]. Of note, 36% of T2DM patients in this study reported the presence of complications including peripheral neuropathy (22.2%), nephropathy (10.4%), cardiovascular (8.0%) and retinopathy (4.8%).…”
Section: Factors Associated With Sleep Qualitysupporting
confidence: 93%
See 2 more Smart Citations
“…Diabetes is a challenge for millions of people in both developed and developing countries. 3 vidence in Ethiopia showed that an estimated 3.8% of the population had DM. 4 Sleep is essential for life and maintenance of body functions.…”
Section: Introductionmentioning
confidence: 99%